2015
DOI: 10.4064/aa168-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic formulae for partition ranks

Abstract: Using an extension of Wright's version of the circle method, we obtain asymptotic formulae for partition ranks similar to formulae for partition cranks which where conjectured by F. Dyson and recently proved by the first author and K. Bringmann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Similar to the present work, these statistics have gained a lot of attention because of their connections to exotic modular objects, such as quasimodular forms and mock modular forms [23,24,67,73]. Significant results about the distribution of these statistics appear notably in the works of Bringmann and Mahlburg and their coauthors [15,21,30,31,69].…”
Section: A History Of Partition Statisticssupporting
confidence: 67%
“…Similar to the present work, these statistics have gained a lot of attention because of their connections to exotic modular objects, such as quasimodular forms and mock modular forms [23,24,67,73]. Significant results about the distribution of these statistics appear notably in the works of Bringmann and Mahlburg and their coauthors [15,21,30,31,69].…”
Section: A History Of Partition Statisticssupporting
confidence: 67%
“…In [10], Dyson conjectured an asymptotic formula for the crank statistic for integer partitions: Bringmann and Dousse [4] proved that (1.1) holds for all |m| ≤ ( √ n log n)/(π √ 6). In [8], Dousse and Mertens proved the same result for N(m, n). For more results on the asymptotics of the rank and crank statistic for integer partitions, see [6,7,13,14].…”
Section: Introductionmentioning
confidence: 56%
“…More recently, Dousse and M. Mertens [10] showed that the same asymptotic formula holds for N (m, n); i.e., the distribution for cranks and ranks are asymptotically similar when m is relatively smaller than n (more precisely, for |m| ≤ √ n log n π √ 6…”
Section: Introductionmentioning
confidence: 76%